Impact of Wii Fit Training (WFT) and Reactive Balance Training (RBT) for in elder age population: A comparative analysis - Mazen AlQahtani (Wolters Kluwer Medknow Publications, 2024)
Objective: This study aims to assess the comparative efficacy of two distinct balancing training intervention strategies, namely, Wii Fit Balance Training (WFT) and Reactive Balance Training (RBT), in reducing older individuals' fear of falling, as well as enhancing their balance and functional mobility. Materials and Methods: One of the two groups was randomly assigned a total of 45 individuals. The first group received Wii Fit training, whereas the second group engaged in reactive balancing challenges. The efficiency of the techniques was evaluated using three outcome measures: the Fullerton Advanced Balance (FAB), Scale Time up and Go Test (TUG), and Berg Balance Scale (BBS). To facilitate the comparison between the groups, an independent student t-test was employed. Results: Both experimental groups showed significant improvements compared to their respective control groups in the research study (BBS: P = 0.023; P = 0.036; FAB: P = 0.027; P = 0.044; and TUG: P = 0.017; P = 0.025). Conclusion: It can be inferred that both reactive balance training and Wii Fit training have the potential to serve as efficacious treatment interventions aimed at mitigating balance deterioration among older individuals.